1975
DOI: 10.1071/zo9750411
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers in the Family Canidae.

Abstract: One quantitative and nine qualitative genetic markers were investigated in some 200 individuals of the family Canidae, including 34 breeds and species. A high degree of homogeneity was observed and only one marker, transferrin, displayed marked variation. The consistent differences were: wolf (one sample), transferrin; jackal (one sample), transferrin and glucosephosphate isomerase; foxes, albumin, transferrin and glucosephsophate isomerase. Two abnormal transferrins were observed in two siblings among six Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…familiaris (Dresler et al, 1976), This paper presents the results of an examination of the amino acid composition of aT-13 (which contains residue 130) of a pure bred dingo. The presence of two forms of a-chain in the dingo further supports the conclusions that the dingo is more closely related to the domestic dog than to the wolf (Glark et al, 1975) or to the coyote (Runkel et al, 1974).…”
supporting
confidence: 69%
“…familiaris (Dresler et al, 1976), This paper presents the results of an examination of the amino acid composition of aT-13 (which contains residue 130) of a pure bred dingo. The presence of two forms of a-chain in the dingo further supports the conclusions that the dingo is more closely related to the domestic dog than to the wolf (Glark et al, 1975) or to the coyote (Runkel et al, 1974).…”
supporting
confidence: 69%
“…The differences of the allele distribution may be attributed to the different genetic origin of the breeds. According to CLARK et al (1975) In most of the investigations the allele a was found to appear more frequently than allele b (DURR, 1969;REETZ, 1983). Only in a few number of breeds including Basenji, Boxer and Greyhound the b allele was the predominating one .…”
Section: Transferrin (Trf)mentioning
confidence: 99%
“…Considerably allele b is only present in breeds of African origin (Azawakh and Sloughi) (Table 3). It may originate from jackal, fox ox coyote (SIMONSEN, 1976;CLARK et al, 1975).…”
Section: Glucose Phosphate Isomerase (Gpi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Early genetic studies used allozymes in an attempt to differentiate canid species in Australia by comparing protein sequences after electrophoresis. However, the results indicated that dingo and dog populations could not be differentiated because there was little genetic variation at the loci tested (Clark, Ryan & Czuppon, 1975;Cole, Baverstock & Green, 1977). The limited biochemical differentiation found in a variety of canid species by Clark et al .…”
Section: Methods Of Assessment Genetic Analysismentioning
confidence: 80%